Method for producing optical laminate
Patent Information
- Application Number
- JP2019221696
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2019-12-06
- Publication Date
- 2025-01-08
- Estimated Expiration
- 2039-12-06
AI Technical Summary
【0018】 本発明の光学積層体は、大面積のマザー基板から切り出したチップの端面に粘着剤層が露出している場合でも、端面に露出した粘着剤に起因する異物の付着やブロッキングが生じ難く、ハンドリング性に優れている。
Smart Images

Figure 0007610347000002 
Figure 0007610347000003 
Figure 0007610347000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical laminate in which an adherend is bonded via a pressure-sensitive adhesive layer. Body It relates to a manufacturing method. [Background technology]
[0002] Transparent adhesive sheets are used to bond optical members in display devices such as liquid crystal displays and organic EL displays, and in display input devices such as touch panels. Transparent adhesive sheets are also used when placing a cover window made of a transparent resin plate, glass plate, or the like on the viewing side surface of an image display device.
[0003] A colored layer for decoration and light shielding is printed on the frame of the cover window, and a printing step of about 10 μm to several tens of μm occurs in the printed part of the colored layer. As described in Patent Document 1, a thick and soft adhesive sheet is used to bond optical components having a printing step to prevent air bubbles from entering the printing step and stress concentration in the printing step.
[0004] In recent years, organic EL panels using bendable substrates (flexible substrates) such as resin films have been put to practical use, and foldable displays that can be folded have also been put to practical use. In a foldable display, bending is performed repeatedly at the same place, so distortion occurs at the bending point and its surroundings. Patent Document 2 proposes softening the adhesive sheet that bonds optical members together to relieve stress distortion in order to prevent device destruction caused by concentration of distortion at the bending point.
[0005] The transparent adhesive sheet used for bonding optical members is generally provided as an adhesive sheet with release films, which are temporarily attached to both sides, and is used by cutting into a predetermined size according to the shape and size of the adherend. For example, for bonding components of an image display device, a sheet of adhesive sheet cut into a size approximately equal to the size of the screen is used. As described in Patent Document 1 and Patent Document 3, the transparent adhesive sheet can also be used by cutting into sheets in a state where it is previously bonded to an optical member such as a polarizing plate. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2014-115468 A [Patent Document 2] JP 2018-45213 A [Patent Document 3] JP 2019-179211 A Summary of the Invention [Problem to be solved by the invention]
[0007] When a thick or soft adhesive is used, the adhesive exposed on the edge of the product (chip) cut into sheets of a specified size is likely to protrude from the edge of the chip, which may cause foreign matter to adhere to the edge or cause contamination of the surroundings. In addition, when multiple chips are stored stacked, the adhesive protrusion from the edge may cause blocking between the adhesive sheets, making it difficult to pick up the adhesive sheets one by one.
[0008] In order to prevent problems caused by the adhesive overflowing from the edge, Patent Document 1 proposes cutting or processing the adhesive layer so that the edge of the adhesive layer is located inside the edge (cut surface) of the release film. The screen shape of an image display device is generally rectangular, but the screen shape of an automobile instrument panel, a smart watch, etc. is a shape other than a rectangle (irregular shape). In addition, in mobile devices such as smartphones, irregular screen shapes with notches on the periphery are adopted in order to arrange cameras and sensors as the bezel-less trend continues.
[0009] In order to manufacture an image display device having a screen with an irregular shape, it is necessary to process each optical component into an irregular shape. In addition, precise alignment is required when bonding each component, which may lead to a decrease in productivity and yield. For this reason, it has been proposed to cut out an irregular shape after bonding multiple optical components such as organic EL cells and polarizing plates together with an adhesive sheet in advance.
[0010] When cutting out chips in this manner while multiple optical components are stacked, it is difficult to process the components so that the end faces of the optical components and release film are aligned with the end faces of the adhesive sheet and the end face of the adhesive layer is positioned inside the laminate.
[0011] In view of the above, the present invention aims to provide an optical laminate in which adhesion of foreign matter or blocking due to the adhesive exposed at the end surface is unlikely to occur, even when the end surface of the adhesive layer is aligned with the end surface of an optical component or a release film. [Means for solving the problem]
[0012] The optical laminate includes a first adherend and a second adherend bonded to both main surfaces of a first pressure-sensitive adhesive layer. The thickness of the first pressure-sensitive adhesive layer may be 30 μm or more. Examples of the adherend include optical films such as polarizing plates, image display cells, cover windows, and release films. The optical laminate may have a polarizing plate in contact with the first pressure-sensitive adhesive layer, and an image display cell such as an organic electroluminescence (EL) cell may be further bonded to the polarizing plate.
[0013] The end face of the first pressure-sensitive adhesive layer preferably has a minimum load of -0.2 μN or more in a load curve measured by nanoindentation, and a displacement of an unloading curve of 8 μm or less. The first pressure-sensitive adhesive layer preferably has a gel fraction of the pressure-sensitive adhesive at the in-plane center of 25% or more.
[0014] The first pressure-sensitive adhesive layer may have different physical properties at the central portion and at the end surfaces of the surface. For example, the first pressure-sensitive adhesive layer may have a end face Minimum load of the load curve Absolute value of but, In-plane center Minimum load of the load curve Absolute value of The first pressure-sensitive adhesive layer may have a thickness of 0.3 times or less as measured by nanoindentation. end face The displacement of the unloading curve is In-plane center The displacement may be 0.5 times or less of the displacement of the unloading curve.
[0015] The first pressure-sensitive adhesive layer may contain an ultraviolet absorbing agent. The pressure-sensitive adhesive constituting the first pressure-sensitive adhesive layer may have photocuring properties.
[0016] The photocurable adhesive may contain, in addition to the base polymer, a monomer or oligomer having a photocurable functional group. Also, a compound having a photocurable functional group may be bonded to the base polymer. The photocurable adhesive may contain a photopolymerization initiator. The photocurable adhesive preferably has a gel fraction of 70% or more after photocuring. The photocurable adhesive preferably has a gel fraction of 1.2 times or more of the gel fraction before photocuring.
[0017] The mother substrate is cut into a predetermined size to obtain a single optical laminate (chip). The mother substrate can also be cut into chips by irradiation with an ultraviolet laser. The optical laminate is formed by cutting the first adhesive layer with an ultraviolet laser at a cutting surface at a minimum load of the load curve of the adhesive. Absolute value ofis preferably 0.3 times or less than before cutting, the displacement of the unloading curve of the adhesive on the cut surface is 0.5 times or less than before cutting, and the indentation elastic modulus of the adhesive on the cut surface is 1.5 to 10 times before cutting. Effect of the Invention
[0018] The optical laminate of the present invention is easy to handle, even when the adhesive layer is exposed on the edge surface of a chip cut out from a large-area mother substrate, as it is less susceptible to adhesion of foreign matter or blocking caused by the adhesive exposed on the edge surface. [Brief description of the drawings]
[0019] [Figure 1] FIG. 2 is a cross-sectional view of an optical laminate according to one embodiment. [Diagram 2] FIG. 2 is a cross-sectional view of an optical laminate according to one embodiment. [Diagram 3] FIG. 2 is a cross-sectional view of an optical laminate according to one embodiment. [Figure 4] FIG. 2 is a cross-sectional view of an optical laminate according to one embodiment. [Diagram 5] FIG. 2 is a cross-sectional view of an optical laminate according to one embodiment. [Figure 6] 1 is an example of a load-displacement curve of an adhesive sheet by nanoindentation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] [Example of stacking configuration of optical laminate] The optical laminate of the present invention is a laminate in which an adherend is bonded to each of the first and second main surfaces of a transparent adhesive sheet. The adherend may be one that is fixedly laminated to the adhesive layer, or one that is peelably attached (temporarily attached).
[0021] 1 is a cross-sectional view of an optical laminate 101 according to one embodiment. The optical laminate 101 is a pressure-sensitive adhesive sheet with release films in which release films 41, 43 are temporarily attached to a first main surface and a second main surface of a pressure-sensitive adhesive layer 21, respectively.
[0022] The optical laminate 102 shown in Fig. 2 is a polarizing plate with a pressure-sensitive adhesive in which a pressure-sensitive adhesive layer 21 is laminated on a first main surface of an optical film 10. The release film 43 is peeled off from the optical laminate 101 shown in Fig. 1, and the optical film 10 is bonded to the second main surface of the exposed pressure-sensitive adhesive layer 21, thereby forming the optical laminate 102.
[0023] The optical laminate 103 shown in Fig. 3 is a polarizing plate with double-sided adhesive in which a first pressure-sensitive adhesive layer 21 is laminated on a first main surface of an optical film 10, and a second pressure-sensitive adhesive layer 22 is laminated on a second main surface of the optical film 10. The optical laminate 103 is formed by laminating the second pressure-sensitive adhesive layer 22 on the second main surface of the optical film 10 of the optical laminate 102 shown in Fig. 2. The first pressure-sensitive adhesive layer 21 may be laminated after the second pressure-sensitive adhesive layer 22 is laminated on the second main surface of the optical film 10, or the first pressure-sensitive adhesive layer 21 and the second pressure-sensitive adhesive layer 22 may be laminated simultaneously on both main surfaces of the optical film 10.
[0024] The optical laminate 104 shown in Fig. 4 is an image display panel having an optical film 10 on the surface of an image display cell 70. The release film 42 is peeled off from the optical laminate 103 shown in Fig. 3, and the image display cell 70 is bonded to the exposed second pressure-sensitive adhesive layer 22, thereby forming the optical laminate 104.
[0025] The optical laminate 105 shown in Fig. 5 is an image display panel having a cover window 80 on the surface of a polarizing plate. The release film 41 is peeled off from the optical laminate 104 shown in Fig. 4, and the cover window 80 is attached to the exposed first main surface of the first pressure-sensitive adhesive layer 21, thereby forming the optical laminate 105.
[0026] The optical laminate may have an adherend laminated on the front and back of the pressure-sensitive adhesive layer 21, and the laminated structure is not limited to the above. As shown in Fig. 3, the optical laminate may further include another pressure-sensitive adhesive layer 22 on the adherend (optical film 10) laminated to the pressure-sensitive adhesive layer 21, or as shown in Fig. 4, an adherend (image display cell 70) may be laminated on the pressure-sensitive adhesive layer 22, or as shown in Fig. 5, an adherend (cover window 80) may be fixed and laminated on the first pressure-sensitive adhesive layer 21. Another adherend may be laminated on the adherend laminated on the first pressure-sensitive adhesive layer 21 via another pressure-sensitive adhesive layer.
[0027] [Characteristics of optical laminate chips] These optical laminates are generally cut into sheets (chips) of a given size after forming a large-sized mother substrate. This method can improve productivity because a large number of sheet products can be obtained from a mother substrate. In a chip cut from an optical laminate in which adherends are attached to both sides of an adhesive sheet, the end faces of the adherends attached to the adhesive and the end faces of the adhesive layer are aligned, and the adhesive layer is exposed at the end faces of the laminate.
[0028] In the optical laminate of the present invention, the end face of the pressure-sensitive adhesive layer 21 has a predetermined characteristic. The characteristic of the end face of the pressure-sensitive adhesive layer can be evaluated by nanoindentation. The nanoindentation method is a technique in which the indenter of a nanoindenter is pressed into a sample to a predetermined depth (loading), and then the indenter is pulled up until it is separated from the sample (unloading), and the mechanical characteristics of the surface of the sample are analyzed from the relationship between the displacement and the load at that time (load-displacement curve).
[0029] Figure 6 is an example of a load-displacement curve of an adhesive sheet measured at a constant loading and unloading rate. When the indenter is brought close to the sample, a negative load (a force that pulls the indenter toward the sample) acts on the indenter as it comes into contact with the sample (point A). The load w at this time is the minimum load on the load curve. The minimum load w on the load curve is the force with which the adhesive layer pulls in adherends such as adherends and foreign objects (the force with which the adhesive adheres to the adherend, adhesion), and reflects the surface tension and wettability of the adhesive. The smaller the minimum load w on the load curve (the larger the absolute value of w), the greater the wettability of the adhesive, and the easier it is to adhere when the adherend comes into contact.
[0030] The indenter is pressed at a constant loading rate until it reaches a specified depth p (point B). The load q at this time is the maximum load on the load curve, and the larger the load q, the harder the adhesive.
[0031] After the indenter is pressed to a depth p, it is pulled up at a constant unloading speed. When the force pulling up the indenter and the force (adhesive force) of the adhesive trying to hold the indenter in place are balanced, the test force decreases, and when the balance between the two is lost, the unloading curve shows a minimum (point C). The load u at this time is the minimum load on the unloading curve, and the higher the adhesive force, the larger the absolute value of the load u.
[0032] If the indenter is further raised, it begins to peel off from the adhesive, and when it is completely peeled off from the adhesive, the load becomes 0 (point D). The absolute value of the displacement at this point, d, is the displacement on the unloading curve. The more easily the adhesive is locally deformed and the greater the stringiness due to constriction or necking, the greater the displacement d on the unloading curve.
[0033] The load-displacement curve of the end face of the adhesive layer of the optical laminate is measured using a conical-spherical indenter (an indenter with a rounded tip) with a tip curvature radius of 10 μm, at a loading / unloading rate of 1000 nN / sec and an indentation depth of 3000 nm.
[0034] The end face of the adhesive layer 21 preferably has a minimum load w of -0.2 μN or more in the load curve. The minimum load w of the load curve is more preferably -0.15 μN or more, even more preferably -0.1 μN or more, and particularly preferably -0.07 μN or more. The larger w (smaller the absolute value of w) and closer to 0, the less sticky the end face of the adhesive layer becomes, and there is a tendency for adhesion of foreign matter and blocking due to contact between the end faces of the chips to be suppressed.
[0035] The end face of the adhesive layer 21 preferably has a displacement d of 8 μm or less in the unloading curve. The displacement d of the unloading curve is preferably 7 μm or less, more preferably 6 μm or less, and even more preferably 5 μm or less. The smaller d and closer to 0, the less likely the adhesive is to deform at the end face of the adhesive layer, and the more likely it is that the adhesive will protrude from the end face due to its flow and that the chips will block each other when multiple chips are stacked.
[0036] From the viewpoint of suppressing flow of the adhesive at the end faces, the indentation modulus of the end faces of the adhesive layer 21 is preferably 0.3 MPa or more, more preferably 0.35 MPa or more, and even more preferably 0.4 MPa or more.
[0037] As described above, in a chip of an optical laminate having the adhesive layer 21 exposed at its end surface, in order to suppress adhesion of foreign matter and blocking between chips caused by the end surface of the adhesive layer, it is preferable that the absolute value of the minimum load w of the load curve and the displacement d of the unloading curve are small at the end surface of the adhesive layer 21.
[0038] On the other hand, the wettability and viscosity of the adhesive are important properties for adhering and holding the adherend, and an adhesive sheet with a small absolute value of the minimum load w of the load curve and a small displacement d of the unload curve may have poor adhesive holding power to the adherend. Therefore, it is preferable that the end face of the adhesive layer 21 locally has the above properties, and it is preferable that the absolute value of the minimum load w of the load curve and the displacement d of the unload curve are larger in the central part of the chip's surface than in the end face. In other words, it is preferable that the absolute value of the minimum load w of the load curve and the displacement d of the unload curve are locally small in the end face (and its vicinity). By locally reducing the absolute value of w and d in the end face, it is possible to reduce adhesion of foreign matter and blocking caused by the exposed end face of the adhesive layer while maintaining the adhesive properties to the adherend.
[0039] In the chip of the optical laminate, the minimum load w of the load curve is preferably -0.2 μN or less, and more preferably -0.25 μN or less, in the in-plane center of the adhesive layer 21. In the in-plane center of the adhesive layer 21, the displacement d of the unload curve is preferably 10 μm or more, more preferably 12 μm or more, and even more preferably 14 μm or more.
[0040] Minimum load w on the load curve of the 21st end surface of the adhesive layer Absolute value of is the minimum load on the load curve at the center of the surface Absolute value of The indentation elastic modulus of the end face of the pressure-sensitive adhesive layer 21 is preferably 1.5 to 10 times, more preferably 2 to 8 times, and even more preferably 2.5 to 7 times that of the indentation elastic modulus ...
[0041] A chip of the optical laminate is cut at the in-plane center so as not to cause any change in the properties of the adhesive, and an indenter is brought into contact with the cut surface, thereby making it possible to carry out nanoindentation measurement of the adhesive at the in-plane center of the adhesive layer 21 of the optical laminate. Alternatively, the measurement may be carried out by peeling the adherend from the adhesive layer and bringing an indenter into contact with the main surface of the adhesive layer.
[0042] In order to reduce the absolute value of the minimum load w of the load curve and the displacement d of the unload curve at the end face while maintaining the adhesive properties of the central portion of the surface of the adhesive layer 21, for example, the adhesive at the end face and its vicinity may be locally modified. For example, the adhesive may be modified by locally heating the end face of the chip. If the adhesive constituting the adhesive layer 21 is curable, the adhesive at the end face and its vicinity may be selectively cured by irradiating the end face with active energy rays such as electron beams or ultraviolet rays. In addition, when cutting out the chip from the motherboard, the adhesive at the cut surface may be modified. For example, if the adhesive constituting the adhesive layer 21 is photocurable, the cutting surface (end face of the chip) and the laser irradiated area in its vicinity can be locally photocured by performing cutting processing with an ultraviolet laser.
[0043] [Components of optical laminate] As described above, the components constituting the optical laminate are optical members bonded to the adhesive layer 21, or optical members bonded via another adhesive, specific examples of which include an optical film, an image display cell, a cover window, etc.
[0044] <Image display cell> 4, the image display cell 70 is a top-emission organic EL cell, and includes a metal electrode 73, an organic light-emitting layer 75, and a transparent electrode 77, which are arranged in this order on a substrate 71. A sealant 79 is laminated on the transparent electrode 77. Although not shown in the figure, the sealant 79 is preferably provided so as to cover the side surfaces of the electrodes 73, 77, and the organic light-emitting layer 75.
[0045] A glass substrate or a plastic substrate is used as the substrate 71. In a top-emission organic EL cell, the substrate 71 does not need to be transparent, and a highly heat-resistant film such as a polyimide film may be used as the substrate 71. When a polyimide film is used as the substrate 71, polyimide has a high ultraviolet absorption, so that the laminate can be cut by irradiating the laminate 104 with an ultraviolet laser from the substrate 71 side. Even if a material other than polyimide is used, cutting by an ultraviolet laser can be easily performed by using a resin material with high ultraviolet absorption such as polyethylene naphthalate (PEN) or a material containing an ultraviolet absorbent as the material of the substrate 71.
[0046] The organic light-emitting layer 75 may include an electron transport layer, a hole transport layer, etc., in addition to an organic layer that itself functions as a light-emitting layer. The transparent electrode 77 is a metal oxide layer or a metal thin film, and transmits light from the organic light-emitting layer 75. A back sheet (not shown) may be provided on the rear side of the substrate 71 for the purpose of protecting and reinforcing the substrate.
[0047] The organic EL cell may be a bottom emission type in which a transparent electrode, an organic light emitting layer, and a metal electrode are laminated in this order on a substrate. In a bottom emission type organic EL cell, a transparent substrate is used, and the substrate is disposed on the viewing side (second adhesive layer 22 side). The image display cell is not limited to an organic EL cell, and may be a liquid crystal cell or an electrophoretic display cell (electronic paper), etc. A touch panel sensor (not shown) may be disposed on the viewing side surface of the image display cell 70.
[0048] <Optical film> An example of the optical film 10 disposed on the viewing side surface of the organic EL cell 70 is a polarizing plate. The polarizing plate includes a polarizer 11, and transparent films 13 and 15 are laminated as polarizer protective films on both sides of the polarizer 11. A pressure-sensitive adhesive layer may be provided directly on the polarizer 11, omitting the polarizer protective films on one or both sides of the polarizer.
[0049] Examples of the polarizer 11 include hydrophilic polymer films such as polyvinyl alcohol films, partially formalized polyvinyl alcohol films, and partially saponified ethylene-vinyl acetate copolymer films, which are uniaxially stretched after adsorbing a dichroic substance such as iodine or a dichroic dye, and polyene-based oriented films such as dehydrated polyvinyl alcohol and dehydrochlorinated polyvinyl chloride.
[0050] A thin polarizer having a thickness of 10 μm or less can also be used as the polarizer 11. Examples of the thin polarizer include polarizers described in JP-A-51-069644, JP-A-2000-338329, WO2010 / 100917, Japanese Patent No. 4691205, and Japanese Patent No. 4751481. The thin polarizer can be obtained by a manufacturing method including, for example, a step of stretching a polyvinyl alcohol-based resin layer and a resin substrate for stretching in a laminated state, and a step of dyeing with a dichroic material such as iodine.
[0051] Transparent resin films such as cellulose resins, cyclic polyolefin resins, acrylic resins, phenylmaleimide resins, polycarbonate resins, etc. are preferably used as the transparent films 13 and 15. When the transparent films 13 and 15 are provided on both sides of the polarizer 11, the transparent films 13 and 15 may be films made of the same resin material or different resin materials.
[0052] The optical film 10 may include an optically functional film laminated on one or both surfaces of the polarizer 11 via an appropriate adhesive layer or pressure-sensitive adhesive layer as necessary. Examples of the optically functional film include a retardation plate, a viewing angle widening film, a viewing angle limiting (anti-peeping) film, and a brightness improving film. The optical film 10 may include a touch panel sensor as the optically functional film. The transparent films 13 and 15 in contact with the polarizer may function as both a polarizer protective film and an optically functional film. The transparent films 13 and 15 may also function as an electrode substrate film for a touch panel sensor.
[0053] The metal electrode 73 of the organic EL cell 70 is light reflective. Therefore, when external light enters the organic EL cell, the light is reflected by the metal electrode 73, and the reflected light is viewed from the outside as a mirror surface. By disposing a circular polarizing plate as the optical film 10 on the viewing side surface of the organic EL cell 70, the reflected light at the metal electrode 73 is prevented from being re-emitted to the outside, and the visibility and design of the screen of the display device can be improved.
[0054] The circular polarizing plate includes a retardation film on the surface of the polarizer 11 facing the organic EL cell 70. The transparent film 15 disposed adjacent to the polarizer 11 may be a retardation film. When the retardation film has a retardation of λ / 4 and the angle between the slow axis direction of the retardation film and the absorption axis direction of the polarizer 11 is 45°, the laminate of the polarizer and the retardation film functions as a circular polarizing plate for suppressing re-emission of reflected light at the metal electrode 73. The retardation film constituting the circular polarizing plate may be a laminate of two or more films. For example, a wideband circular polarizing plate that functions as a circular polarizing plate over a wide band of visible light can be obtained by laminating a polarizer, a λ / 2 plate, and a λ / 4 plate so that their optical axes form a predetermined angle.
[0055] <Cover window> A transparent plate having appropriate mechanical strength and thickness is used as the cover window 80. Such a transparent plate may be a transparent resin plate such as an acrylic resin, a polycarbonate resin, or a transparent polyimide resin, or a glass plate. The thickness of the cover window 80 is, for example, about 20 to 2000 μm. In a flexible device, it is preferable to use a transparent resin film as the cover window 80, and the thickness thereof is preferably 20 to 500 μm, more preferably 30 to 300 μm, and further preferably 50 to 200 μm. A bendable thin glass substrate may be used as the cover window 80.
[0056] The cover window 80 may be integrated with a touch panel sensor. An anti-reflection layer, a hard coat layer, or the like may be provided on the viewing side surface of the cover window 80.
[0057] <Release film> The release films 41, 42, 43 temporarily attached to the pressure-sensitive adhesive layers 21, 22 preferably have a release layer on the surface of the film substrate. Examples of materials for the release layer include silicone-based release agents, fluorine-based release agents, long-chain alkyl-based release agents, and fatty acid amide-based release agents. Silicone release agents are preferred because they can achieve both adhesion to acrylic pressure-sensitive adhesives and releasability.
[0058] The film substrate of the release film is preferably a resin film having transparency. Examples of the resin material include polyester resins such as polyethylene terephthalate and polyethylene naphthalate, acetate resins, polyethersulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, polyvinyl chloride resins, polyvinylidene chloride resins, polystyrene resins, polyvinyl alcohol resins, polyarylate resins, and polyphenylene sulfide resins. Among these, polyester resins such as polyethylene terephthalate (PET) are particularly preferred. The thickness of the release film is preferably 10 to 200 μm, more preferably 25 to 150 μm.
[0059] <First adhesive layer> The first pressure-sensitive adhesive layer 21 is a layer of pressure-sensitive adhesive. In the optical laminate shown in Figs. 2 to 5, the first pressure-sensitive adhesive layer 21 is disposed on the viewing side of the optical film 10, and is used to bond the optical film 10 to a transparent member such as a cover window 80.
[0060] The pressure-sensitive adhesive layer 21 is preferably transparent and has low visible light absorption. The total light transmittance of the pressure-sensitive adhesive layer 21 is preferably 85% or more, more preferably 90% or more. The haze of the pressure-sensitive adhesive layer 21 is preferably 2% or less, more preferably 1% or less. The total light transmittance and haze are measured using a haze meter in accordance with JIS K7136.
[0061] The adhesive constituting the adhesive layer 21 can be appropriately selected and used from those having a base polymer such as an acrylic polymer, a silicone polymer, a polyester, a polyurethane, a polyamide, a polyvinyl ether, a vinyl acetate / vinyl chloride copolymer, a modified polyolefin, an epoxy-based, a fluorine-based, or a rubber-based polymer.
[0062] An acrylic adhesive having an acrylic polymer as a base polymer is preferably used as the adhesive constituting the adhesive layer 21, since it has excellent optical transparency, shows adhesive properties such as moderate wettability, cohesiveness and adhesion, and is also excellent in weather resistance, heat resistance, etc. The content of the acrylic base polymer in the total solid content of the adhesive composition of the acrylic adhesive is preferably 50 wt % or more, more preferably 70 wt % or more, and even more preferably 80 wt % or more.
[0063] The acrylic base polymer is preferably one having a monomer unit of (meth)acrylic acid alkyl ester as the main skeleton. In this specification, "(meth)acrylic" means acrylic and / or methacrylic.
[0064] As the (meth)acrylic acid alkyl ester, a (meth)acrylic acid alkyl ester having an alkyl group with 1 to 20 carbon atoms is preferably used. The (meth)acrylic acid alkyl ester may have a branched alkyl group. The content of the (meth)acrylic acid alkyl ester is preferably 40% by weight or more, more preferably 50% by weight or more, and even more preferably 60% by weight or more, based on the total amount of the monomer components constituting the base polymer. The acrylic base polymer may be a copolymer of a plurality of (meth)acrylic acid alkyl esters. The arrangement of the constituent monomer units may be random or block.
[0065] The acrylic base polymer may contain an acrylic monomer unit having a crosslinkable functional group as a copolymerization component. When the base polymer has a crosslinkable functional group, the gel fraction of the adhesive can be easily increased by thermal crosslinking or photocuring of the base polymer. Examples of acrylic monomers having a crosslinkable functional group include hydroxyl group-containing monomers and carboxyl group-containing monomers. Among them, it is preferable to contain a hydroxyl group-containing monomer as a copolymerization component of the base polymer. When the base polymer has a hydroxyl group-containing monomer as a monomer unit, the crosslinking property by an isocyanate crosslinking agent or the like is enhanced, and the opacity of the adhesive in a high temperature and high humidity environment tends to be suppressed, and an adhesive with high transparency can be obtained.
[0066] Examples of hydroxy group-containing monomers include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and (4-hydroxymethyl)cyclohexylmethyl (meth)acrylate.
[0067] The content of the hydroxy group-containing monomer is preferably from 0.1 to 50% by weight, more preferably from 1 to 40% by weight, and even more preferably from 3 to 30% by weight, based on the total amount of monomer components constituting the base polymer.
[0068] The acrylic base polymer preferably contains a highly polar monomer unit such as a nitrogen-containing monomer in addition to the hydroxyl group-containing monomer unit. By containing a highly polar monomer such as a nitrogen-containing monomer in addition to the hydroxyl group-containing monomer, the pressure-sensitive adhesive has high adhesion and holding power, and is suppressed from becoming cloudy under high temperature and high humidity conditions.
[0069] Examples of the nitrogen-containing monomer include vinyl monomers such as N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, (meth)acryloylmorpholine, N-vinylcarboxylic acid amides, and N-vinylcaprolactam, and cyanoacrylate monomers such as acrylonitrile and methacrylonitrile. Among these, N-vinylpyrrolidone and (meth)acryloylmorpholine are preferably used.
[0070] The content of the nitrogen-containing monomer is preferably from 0.1 to 50% by weight, more preferably from 1 to 40% by weight, and even more preferably from 3 to 30% by weight, based on the total amount of monomer components constituting the base polymer.
[0071] The monomer components forming the acrylic polymer may contain a polyfunctional monomer component. The polyfunctional monomer is a monomer having at least two polymerizable functional groups having an unsaturated double bond, such as a (meth)acryloyl group or a vinyl group. The polyfunctional monomer may have three or more polymerizable functional groups in one molecule.
[0072] The base polymer can be prepared by a known polymerization method such as solution polymerization, UV polymerization, bulk polymerization, emulsion polymerization, etc. In terms of the transparency, water resistance, cost, etc. of the adhesive, the solution polymerization method or UV polymerization is preferred. Ethyl acetate, toluene, etc. are generally used as a solvent for solution polymerization. When preparing the base polymer, a polymerization initiator such as a photopolymerization initiator or a thermal polymerization initiator may be used depending on the type of polymerization reaction. A chain transfer agent may be used to adjust the molecular weight of the base polymer.
[0073] From the viewpoint of providing the pressure-sensitive adhesive with appropriate adhesive retention and flexibility, the weight-average molecular weight of the base polymer is preferably from 200,000 to 1,000,000, and more preferably from 250,000 to 800,000. The molecular weight of the base polymer refers to the molecular weight of the polymer before the introduction of a crosslinked structure.
[0074] The base polymer may have a crosslinked structure. By introducing a crosslinked structure into the base polymer, the cohesive force of the adhesive is increased, and the adhesiveness to the adherend is improved. The crosslinked structure is formed, for example, by adding a crosslinking agent after polymerization of the base polymer. As the crosslinking agent, a commonly used one such as an isocyanate-based crosslinking agent, an epoxy-based crosslinking agent, an oxazoline-based crosslinking agent, an aziridine-based crosslinking agent, a carbodiimide-based crosslinking agent, or a metal chelate-based crosslinking agent can be used. The content of the crosslinking agent is usually in the range of 0.01 to 5 parts by weight, preferably 0.05 to 3 parts by weight, and more preferably 0.07 to 2.5 parts by weight, relative to 100 parts by weight of the acrylic base polymer. The more the amount of the crosslinking agent added, the higher the gel fraction of the adhesive tends to be.
[0075] The adhesive constituting the adhesive layer 21 may have photocuring properties. For example, if a photocuring adhesive is used to bond an adherend (e.g., a cover window) having a printed step due to decorative printing or the like, it is possible to provide step-following properties by performing bonding while the adhesive is in a soft state before photocuring, and the adhesive is photocured by irradiating it with ultraviolet light or the like after bonding, thereby improving adhesion reliability. In addition, if the adhesive has photocuring properties, when cutting the optical laminate by irradiating a laser to cut out chips, the cut surface (end surface of the chip) and its vicinity can be locally photocured, thereby reducing the absolute value of the minimum load w of the load curve and the displacement d of the unloading curve at the end surface while maintaining the adhesive properties of the central part of the surface of the adhesive layer 21.
[0076] The photocurable adhesive preferably contains, for example, a photocurable compound (monomer or oligomer having a photopolymerizable functional group) in addition to a base polymer. The base polymer may be made photocurable by introducing a photopolymerizable functional group.
[0077] The photocurable compound preferably contains a polyfunctional polymerizable compound having two or more polymerizable functional groups in one molecule. Examples of the polyfunctional polymerizable compound include a compound having two or more ethylenically unsaturated groups in one molecule, and a compound having one C=C bond and a polymerizable functional group such as epoxy, aziridine, oxazoline, hydrazine, or methylol. Among them, a compound having two or more ethylenically unsaturated groups in one molecule, such as a polyfunctional (meth)acrylate, is preferable. Specific examples of the polyfunctional polymerizable compound include polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, bisphenol A ethylene oxide modified di(meth)acrylate, bisphenol A propylene oxide modified di(meth)acrylate, alkanediol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, ethoxylated isocyanuric acid triacrylate, pentaerythritol tri(meth)acrylate, pentaerythritol di(meth)acrylate, acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, ethoxylated pentaerythritol tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol poly(meth)acrylate, dipentaerythritol hexa(meth)acrylate, neopentyl glycol di(meth)acrylate, glycerin di(meth)acrylate, urethane (meth)acrylate, epoxy (meth)acrylate, butadiene (meth)acrylate, isoprene (meth)acrylate, and the like.
[0078] The amount of the photocurable compound used varies depending on the molecular weight, the number of functional groups, etc., but is preferably 0.3 to 10 parts by weight, more preferably 0.5 to 5 parts by weight, per 100 parts by weight of the base polymer. The more the amount of the photocurable compound added, the easier it is for the adhesive at the cut surface to harden upon laser irradiation, and the absolute value of the minimum load w of the load curve at the end surface and the displacement d of the unload curve tend to become smaller.
[0079] A method for introducing a photopolymerizable functional group into a base polymer includes mixing a compound having a functional group capable of bonding with a functional group (such as a hydroxy group or a carboxy group) of the base polymer and a radically polymerizable functional group with the base polymer.
[0080] The photocurable adhesive preferably contains a photopolymerization initiator in addition to the photocurable compound and / or the polymer having a photopolymerizable functional group introduced therein. Examples of the photopolymerization initiator include benzoin ether-based photopolymerization initiators, acetophenone-based photopolymerization initiators, α-ketol-based photopolymerization initiators, aromatic sulfonyl chloride-based photopolymerization initiators, photoactive oxime-based photopolymerization initiators, benzoin-based photopolymerization initiators, benzyl-based photopolymerization initiators, benzophenone-based photopolymerization initiators, ketal-based photopolymerization initiators, thioxanthone-based photopolymerization initiators, and acylphosphine oxide-based photopolymerization initiators. The amount of the photopolymerization initiator added is preferably 0.01 to 5 parts by weight, more preferably 0.05 to 3 parts by weight, based on 100 parts by weight of the base polymer.
[0081] In addition to the above-listed components, the adhesive may contain additives such as a silane coupling agent, a tackifier, a plasticizer, a softener, an anti-degradation agent, a filler, a colorant, an antioxidant, a surfactant, and an antistatic agent.
[0082] The adhesive may contain an ultraviolet absorbing agent. If the adhesive layer 21 has ultraviolet absorbing properties, when the optical laminate is cut by irradiation with an ultraviolet laser, the adhesive layer 21 absorbs the energy of the laser light, so that the cutting processability of the optical laminate is improved and problems such as poor processing and peeling of the adherend tend to be suppressed. The light transmittance of the first adhesive layer 21 at a wavelength of 355 nm may be 80% or less or 75% or less. The content of the ultraviolet absorbing agent in the adhesive layer 21 is, for example, about 0.01 to 10% by weight.
[0083] Examples of the ultraviolet absorber include benzotriazole-based ultraviolet absorbers, benzophenone-based ultraviolet absorbers, triazine-based ultraviolet absorbers, salicylate-based ultraviolet absorbers, cyanoacrylate-based ultraviolet absorbers, etc. Triazine-based ultraviolet absorbers and benzotriazole-based ultraviolet absorbers are preferred because they have high ultraviolet absorption and excellent compatibility with acrylic polymers, and are easy to obtain a highly transparent acrylic adhesive sheet, and among them, triazine-based ultraviolet absorbers containing a hydroxyl group and benzotriazole-based ultraviolet absorbers having one benzotriazole skeleton in one molecule are preferred.
[0084] The adhesive layer is formed by applying the adhesive composition in a layer on the substrate, and drying the solvent or crosslinking and curing the base polymer as necessary. The thickness of the adhesive layer 21 is not particularly limited, and is generally about 5 to 1000 μm. When the adhesive layer 21 is required to have step conformability and stress relaxation properties, the thickness of the adhesive layer 21 is preferably 30 μm or more. The thickness of the adhesive layer 21 may be 40 μm or more or 50 μm or more. From the viewpoint of making the display device lighter and thinner, the ease of forming the adhesive layer, handling properties, etc., the thickness of the adhesive layer 21 is preferably 500 μm or less, more preferably 300 μm or less, and even more preferably 250 μm or less.
[0085] From the viewpoint of providing flexibility, the storage modulus G' of the adhesive layer 21 at 25°C is preferably 0.35 MPa or less, more preferably 0.30 MPa or less, and even more preferably 0.20 MPa or less. On the other hand, if the adhesive layer 21 is too soft, adhesion of foreign matter or chip blocking due to the adhesive exposed at the end surface may occur. Therefore, the storage modulus G' of the first adhesive layer 21 at 25°C is preferably 0.01 MPa or more, more preferably 0.02 MPa or more. The storage modulus G' of the first adhesive layer 21 at 25°C may be 0.03 MPa or more, 0.05 MPa or more, or 0.1 MPa or more.
[0086] The gel fraction of the adhesive layer 21 is preferably 25% or more. If the gel fraction is too low, the adhesive exposed on the end face may cause adhesion of foreign matter or chip blocking. As will be described in detail later, the greater the gel fraction of the adhesive layer 21, the smaller the absolute value of the minimum load w of the load curve and the displacement d of the unload curve of the cut surface (end face) by laser processing tend to be. The gel fraction of the adhesive layer 21 is preferably 30% or more, more preferably 35% or more, even more preferably 40% or more, and may be 45% or more.
[0087] The gel fraction of an adhesive can be determined as the insoluble portion in a solvent such as ethyl acetate, specifically, the weight fraction (unit: weight %) of the insoluble portion after immersing the adhesive in ethyl acetate for 7 days at 23°C relative to the sample before immersion. In general, the gel fraction of a polymer is equal to the degree of crosslinking, and the more crosslinked portions in the polymer, the higher the gel fraction. The gel fraction (amount of crosslinked structure introduced) can be adjusted to a desired range by the method of introducing the crosslinked structure, the type and amount of the crosslinking agent, etc.
[0088] When the adhesive is photocurable, the gel fraction of the photocured adhesive layer 21 is preferably 70% or more. The gel fraction of the photocured adhesive layer 21 is preferably 1.2 times or more, and may be 1.3 times or more, 1.4 times or more, or 1.5 times or more, of the gel fraction before photocuring.
[0089] <Second adhesive layer> The second pressure-sensitive adhesive layer 22 is a layer of pressure-sensitive adhesive. In the optical laminate shown in FIGS.
[0090] The second adhesive layer is preferably transparent and has low visible light absorption. The total light transmittance of the adhesive layer 22 is preferably 85% or more, more preferably 90% or more. The haze of the adhesive layer 22 is preferably 2% or less, more preferably 1% or less.
[0091] There are no particular limitations on the adhesive constituting the adhesive layer 22, and any adhesive having various polymers as a base polymer may be appropriately selected and used. As described above, the adhesive constituting the second adhesive layer 22 is preferably an acrylic adhesive having an acrylic polymer as a base polymer.
[0092] The thickness of the adhesive layer 22 is not particularly limited. The second adhesive layer 22 is not required to have the same thickness or flexibility as the first adhesive layer 21. The thickness of the adhesive layer 22 is, for example, about 3 to 50 μm, and may be 5 to 35 μm, or 10 to 25 μm. The storage modulus G' of the adhesive layer 22 at 25° C. is, for example, about 0.02 to 5 MPa. The adhesive layer 22 is thinner than the adhesive layer 22, and is less susceptible to adhesion of foreign matter or blocking due to the adhesive exposed at the end surface. Therefore, the adhesive properties of the end surface of the second adhesive layer are not particularly limited.
[0093] [Cutting the optical laminate] The components of the optical laminate are laminated via the adhesive layer to form a mother substrate of the optical laminate. The lamination may be performed by either the roll-to-roll method or the batch method. The roll-to-roll method and the batch method may be used in combination. For example, adhesive layers 21, 21 (and release films 41, 42) may be laminated on both sides of the optical film 10 by the roll-to-roll method to prepare a polarizing plate with double-sided adhesive, which may then be cut into a sheet, and the adhesive layer 22 of the polarizing plate with double-sided adhesive may be attached to the image display cell 70 formed in a sheet shape. The lamination of the image display cell may be performed by the roll-to-roll method.
[0094] A chip of the optical laminate is obtained by cutting out a sheet of a predetermined size from the mother substrate of the optical laminate. The shape of the chip is not particularly limited, and may be rectangular, polygonal, rounded polygonal, round, etc., or may have a shape with a notch on the periphery.
[0095] As described above, the chip of the optical laminate exhibits predetermined physical properties in nanoindentation measurement of the end face of the adhesive layer 21, so that adhesion of foreign matter to the end face of the chip and blocking are less likely to occur, and the chip has excellent handleability.
[0096] The method of cutting the optical laminate is not particularly limited, and examples thereof include a method of punching using a Thomson blade or the like, a method of using a cutter such as a round blade or a countersunk blade, a method of using laser light or water pressure, etc. Laser cutting is preferable because it is possible to locally harden the adhesive at the cut surface and its vicinity. When the adhesive layer 21 is made of a photocurable adhesive, the absolute value of the minimum load w of the load curve at the end surface and the displacement d of the unload curve can be reduced by photocuring the end surface of the adhesive layer 21 while cutting the optical laminate with an ultraviolet laser.
[0097] The ultraviolet laser is not particularly limited as long as it can irradiate laser light with a wavelength of 400 nm or less, but the third harmonic of a YAG laser (wavelength 355 nm) is preferred because it has high output and excellent processability. The laser power is, for example, about 0.1 to 50 W.
[0098] The laser may be irradiated from any surface of the optical laminate. It is preferable that the component placed on the laser irradiated surface has absorptivity for laser light. For example, when the optical laminate 101 shown in FIG. 1 is cut by an ultraviolet laser, it is preferable that the release films 41, 43 placed on the laser irradiated surface have ultraviolet absorbing properties. When the optical laminate 102 shown in FIG. 2 is cut by irradiating an ultraviolet laser from the optical film 10 side, it is preferable that the transparent film 15 has ultraviolet absorbing properties. When the optical laminate 104 shown in FIG. 4 is cut by irradiating an ultraviolet laser from the image display cell 70 side, it is preferable that the substrate 71 has ultraviolet absorbing properties.
[0099] In order to give ultraviolet absorbing properties to the film or adhesive layer, an ultraviolet absorbing agent may be added to the resin material. Alternatively, a resin material having ultraviolet absorbing properties, such as a polyimide film or polyethylene naphthalate, may be used. For example, in the optical laminates 104 and 105 shown in FIG. 4 and FIG. 5, if the substrate 71 of the image display cell 70 is a polyimide film, the polyimide film generates heat and vaporizes by irradiating an ultraviolet laser from the image display cell 70 side, and the image display cell 70 and the second adhesive layer 22, optical film 10, first adhesive layer 21, and release film 41 or cover window 80 provided thereon are blown away together with the vapor, forming a through hole penetrating the optical laminate. By moving the optical laminate relative to the laser light source, a cutting line in which the through holes are connected is formed. By forming a cutting line along the periphery of the chip shape, a chip of a predetermined shape is cut out.
[0100] Members other than the laser irradiated surface may also have ultraviolet absorbing properties. For example, if the adhesive layer 21 has ultraviolet absorbing properties, the adhesive layer 21 absorbs the ultraviolet laser, and therefore, even if the adhesive layer 21 is thick and soft, it exhibits good processability. In addition, if the adhesive layer 21 has ultraviolet absorbing properties, the release film 41 and the cover window 80 temporarily attached on the adhesive layer 21 are also processed by the force of heating and vaporization during processing, so that peeling of the adherend and inclusion of air bubbles can be suppressed around the laser irradiated area.
[0101] In the chip of the optical laminate cut by laser, the adhesive layer 21 has locally different viscous behavior at the end face and the laser irradiated area in the vicinity thereof. It is preferable that the absolute value of the minimum load w of the load curve and the displacement d of the unload curve of the adhesive layer 21 are large at the center of the surface, and that the absolute value of the minimum load w of the load curve and the displacement d of the unload curve of the adhesive layer 21 are small at the end face cut by irradiation of the laser beam.
[0102] At the cut surface by laser irradiation, plasticization occurs due to molecular scission. On the other hand, since active species such as radicals are generated by laser irradiation, a hardening action due to the generation of cross-linked structures between polymer chains also occurs. When the gel fraction of the adhesive is small, a large number of low molecular weight molecular chains that are not cross-linked are generated by molecular scission, so the plasticization action tends to be large. On the other hand, if the cross-linked structure remains even if the molecular chains are cut, low molecular weight components are not generated, so when the gel fraction (degree of cross-linking) of the adhesive is large, the effect of hardening due to radical reactions tends to be larger than plasticization due to molecular scission. Therefore, the larger the gel fraction of the adhesive layer 21, the smaller the absolute value of the minimum load w of the load curve and the displacement d of the unloading curve at the laser-processed end face tend to be.
[0103] When the adhesive has photocurability, photocuring of the adhesive by laser irradiation also affects the characteristics of the cut surface. In particular, when the adhesive layer 21 made of a photocurable adhesive composition containing a photocurable monomer and a photopolymerization initiator is cut by irradiation with an ultraviolet laser, the adhesive layer 21 undergoes local photocuring at the end surface and the area nearby where the laser is irradiated. Therefore, the absolute value of the minimum load w of the load curve and the displacement d of the unload curve at the laser-processed end surface tend to become smaller.
[0104] As described above, in the chip of the optical laminate, the minimum load w of the load curve at the central portion of the surface of the adhesive layer 21 is preferably -0.2 μN or less, more preferably -0.25 μN or less. At the end face of the adhesive layer 21, the minimum load of the load curve is preferably -0.2 μN or more, more preferably -0.15 μN or more, even more preferably -0.1 μN or more, and particularly preferably -0.07 μN or more. The minimum load of the load curve at the end face of the adhesive layer 21 Absolute value of is the minimum load on the load curve at the center of the surface Absolute value ofIt is preferably 0.3 times or less, more preferably 0.2 times or less, and even more preferably 0.1 times or less. In other words, in the optical laminate (mother substrate) before being cut into chips, the minimum load of the load curve of the pressure-sensitive adhesive layer 21 is -0.2 μN or less, and it is preferable that the absolute value of the minimum load of the load curve of the cut surface when cut by irradiation with an ultraviolet laser is 0.3 times or less.
[0105] In the chip of the optical laminate, the displacement d of the unloading curve at the in-plane center of the adhesive layer 21 is preferably 10 μm or more, more preferably 12 μm or more, and even more preferably 14 μm or more. At the end face of the adhesive layer 21, the displacement of the unloading curve is preferably 8 μm or less, more preferably 7 μm or less, even more preferably 6 μm or less, and particularly preferably 5 μm or less. The displacement of the unloading curve at the end face of the adhesive layer 21 is preferably 0.5 times or less, more preferably 0.4 times or less, and even more preferably 0.3 times or less, of the displacement of the unloading curve at the in-plane center. In other words, in the optical laminate (mother substrate) before being cut into chips, the displacement of the unloading curve of the adhesive layer 21 is preferably 10 μm or more, and the displacement of the unloading curve of the cut surface when cut by irradiation with an ultraviolet laser is preferably 0.5 times or less.
[0106] In the chip of the optical laminate, the indentation elastic modulus at the in-plane center of the adhesive layer 21 is preferably 0.05 to 0.3 MPa, more preferably 0.1 to 0.25 MPa. The indentation elastic modulus at the end face of the adhesive layer 21 is preferably 0.3 MPa or more, more preferably 0.35 MPa or more, and even more preferably 0.4 MPa or more. The indentation elastic modulus at the end face of the adhesive layer 21 is preferably 1.5 to 10 times, more preferably 2 to 8 times, and even more preferably 2.5 to 7 times, the indentation elastic modulus at the in-plane center of the adhesive layer 21 in the optical laminate (mother substrate) before being cut into chips. In other words, the indentation elastic modulus of the adhesive layer 21 is 0.05 to 0.3 MPa, and it is preferable that the indentation elastic modulus of the cut surface when cut by irradiation with an ultraviolet laser is 1.5 to 10 times.
[0107] As described above, when the gel fraction of the adhesive layer 21 is high and the adhesive is photocurable, the effect of hardening becomes greater than the effect of plasticization due to molecular cutting during laser processing, and the absolute value of the minimum load on the load curve and the displacement of the unloading curve of the cut surface due to laser processing tend to become smaller, and the indentation elastic modulus tends to increase.
[0108] [Formation of display device] The optical laminate processed into a chip shape may further have other members laminated thereon as necessary. For example, in the chip of the optical laminate 104 shown in Fig. 4, the release film 41 temporarily attached to the adhesive layer 21 may be peeled off, and an adherend such as a cover window 80 may be attached to form an image display device.
[0109] After the cover window 80 is laminated onto the first adhesive layer 21, a treatment such as heating, pressurization, or decompression may be performed to remove air bubbles at the lamination interface or near the printing step. An autoclave treatment may be performed for the purpose of suppressing delay bubbles. When the adhesive layer 21 is a photocurable adhesive, the adhesive may be photocured after the cover window 80 is laminated onto the adhesive layer 21. As described above, the adhesive on the end surface of the adhesive layer 21 may be locally photocured during cutting processing with an ultraviolet laser, but the adhesive is uncured in other regions. By photocuring the adhesive layer 21, the adhesive reliability to the adherend such as the cover window 80 can be improved. EXAMPLES
[0110] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0111] [Preparation of adhesive sheet] <Production Example 1> (Preparation of Base Polymer) In a reaction vessel, 64 parts by weight of butyl acrylate (BA), 6 parts by weight of cyclohexyl acrylate (CHA), 10 parts by weight of isostearyl acrylate (ISA), 5 parts by weight of N-vinylpyrrolidone (NVP), and 15 parts by weight of 4-hydroxybutyl acrylate (4HBA), as well as 0.2 parts by weight of azobisisobutyronitrile (AIBN) as a thermal polymerization initiator, were added together with 139 parts by weight of ethyl acetate, and the mixture was stirred for 1 hour under a nitrogen atmosphere at 23°C, followed by nitrogen substitution. The mixture was then reacted at 65°C for 5 hours, followed by 2 hours at 70°C, to prepare an acrylic-based polymer solution. The weight-average molecular weight of the resulting polymer was 450,000.
[0112] (Preparation of Adhesive Composition and Fabrication of Adhesive Sheet) To the base polymer solution, 0.27 parts by weight of trimethylolpropane xylylene diisocyanate (Mitsui Chemicals' "Takenate D110N") as an isocyanate crosslinking agent, 2.5 parts by weight of polypropylene glycol (#400) diacrylate (Shin-Nakamura Chemical's "APG400") as a multifunctional acrylate, and 2.2 parts by weight of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (Nippon Kayaku's "KAYARAD DPHA"), 0.22 parts by weight of IRM Resins' "Ominirad 184" as a photopolymerization initiator, and 0.33 parts by weight of Shin-Etsu Chemical's "KBM-403" as a silane coupling agent were added relative to 100 parts by weight of the polymer, and the mixture was mixed uniformly to prepare a pressure-sensitive adhesive composition (solution). The adhesive composition was applied onto the release-treated surface of a 75 μm-thick separator so that the dried thickness would be 150 μm, and the adhesive composition was dried at 130° C. for 3 minutes to remove the solvent. Then, the release-treated surface of another separator was superimposed on the adhesive layer to obtain adhesive sheet A with separators temporarily attached to both sides.
[0113] <Production Example 2> (Preparation of Base Polymer) Into a reaction vessel, 60 parts by weight of BA, 6 parts by weight of CHA, 1 part by weight of ISA, 18 parts by weight of NVP, and 15 parts by weight of 4HBA as monomer components, and 0.2 parts by weight of AIBN as a thermal polymerization initiator were charged together with 139 parts by weight of ethyl acetate, and the mixture was stirred for 1 hour under a nitrogen atmosphere at 23°C, and nitrogen substitution was performed. Then, the mixture was reacted at 65°C for 5 hours, and then at 70°C for 2 hours to prepare an acrylic polymer solution. The weight average molecular weight of the obtained polymer was 300,000.
[0114] (Preparation of Adhesive Composition and Fabrication of Adhesive Sheet) To the solution of the base polymer, 0.27 parts by weight of "Takenate D110N" as an isocyanate crosslinking agent, 1 part by weight of "APG400" as a multifunctional acrylate, and 2.2 parts by weight of "KAYARAD DPHA", 0.22 parts by weight of "Ominirad 651" manufactured by IRM Resins as a photopolymerization initiator, 0.02 parts by weight of "Tinuvin 384-2" manufactured by BASF as an ultraviolet absorber, and 0.33 parts by weight of "KBM-403" manufactured by Shin-Etsu Chemical Co., Ltd. were added relative to 100 parts by weight of the polymer, and the mixture was mixed uniformly to prepare a pressure-sensitive adhesive composition (solution). Using this pressure-sensitive adhesive composition, a pressure-sensitive adhesive sheet B having a thickness of 150 μm was produced in the same manner as in Preparation Example 1.
[0115] <Preparation Example 3> In preparing the adhesive composition, the amount of the isocyanate crosslinking agent (Takenate D110N) was changed to 0.05 parts by weight, the amount of "APG400" was changed to 3 parts by weight, and the amount of "KAYARAD DPHA" was changed to 1 part by weight. Otherwise, the same procedure as in Preparation Example 2 was repeated to prepare an adhesive sheet C having a thickness of 150 μm.
[0116] <Preparation Example 4> In the preparation of the adhesive composition, the amount of the isocyanate-based crosslinking agent (Takenate D110N) was changed to 0.08 parts by weight, and the multifunctional acrylate and the photopolymerization initiator were not added. Otherwise, the same procedure as in Preparation Example 2 was repeated to prepare an adhesive sheet D having a thickness of 150 μm.
[0117] <Example 5> Using ethyl acetate as a solvent, 97 parts by weight of butyl acrylate (BA) and 3 parts by weight of acrylic acid (AA) were polymerized in the presence of a thermal polymerization initiator (AIBN) to obtain a solution of a polymer with a weight average molecular weight (Mw) of 1.1 million. To this solution, 0.8 parts by weight of trimethylolpropane tolylene diisocyanate (Tosoh's "Coronate L") as an isocyanate-based crosslinking agent and 0.1 parts of a silane coupling agent (Shin-Etsu Chemical's "KBM-403") were added per 100 parts by weight of the polymer, and the mixture was mixed uniformly to prepare a pressure-sensitive adhesive composition (solution). This composition was applied to the release-treated surface of a separator with a thickness of 38 μm so that the thickness after drying was 20 μm, and the composition was dried at 100° C. for 3 minutes to remove the solvent, and then the release-treated surface of another separator was superimposed on the pressure-sensitive adhesive layer, and the mixture was heated at 50° C. for 48 hours to perform a crosslinking treatment, and a pressure-sensitive adhesive sheet P with a thickness of 30 μm and a separator temporarily attached to both sides was obtained.
[0118] [Preparation of laminate A] Using a roll laminator, adhesive sheet A was laminated to one side (on the hard coat layer) of a polarizing plate having a thickness of about 75 μm, and adhesive sheet P was laminated to the other side to obtain a long polarizing plate with double-sided adhesive. The polarizing plate used was one in which a triacetyl cellulose film (32 μm) provided with a hard coat layer was laminated to one side of a polarizer made of a 12 μm-thick stretched polyvinyl alcohol film impregnated with iodine, and a triacetyl cellulose film (31 μm) provided with a coating retardation layer was laminated to the other side of the polarizer.
[0119] The release film on the surface of adhesive sheet P was peeled off, and a 25 μm thick polyimide film (Kapton EN100, manufactured by Toray DuPont) was laminated to the surface of adhesive sheet P by roll-to-roll bonding to obtain a laminate of polyimide film (25 μm) / adhesive sheet P (30 μm) / polarizing plate (75 μm) / adhesive sheet A (150 μm) / separator (75 μm).
[0120] [Preparation of laminates B to D] Except for using adhesive sheets B to D instead of adhesive sheet A, an optical laminate was produced in the same manner as in the production of laminate A, in which a polyimide film was bonded to one side of a polarizing plate via a 30 μm-thick adhesive sheet P, and the other side of the polarizing plate was provided with a 150 μm-thick adhesive sheet with a release film temporarily attached thereon.
[0121] [Cutting optical laminates] The above optical laminate was cut by two different methods into a 40 mm×60 mm rectangle with rounded corners (curvature radius of corners: 7 mm). <Cutting with a blade> The optical stack was punched out using a Thompson blade. <Cutting with ultraviolet laser> The polyimide film was irradiated with a YAG third harmonic ultraviolet laser (wavelength 355 nm, frequency 40 Hz, output 0.4 W) while moving at a scanning speed of 10 mm / sec, to cut out an optical laminate.
[0122] [evaluation] <Gel fraction of adhesive> Approximately 1 g of adhesive was collected from each of the adhesive sheets A to D, wrapped in a porous polytetrafluoroethylene film ("NTF-1122" manufactured by Nitto Denko) with a pore diameter of 0.2 μm cut to a size of 100 mm x 100 mm, and the opening of the wrapping was tied with a string. The weight of the adhesive sample (B) was calculated by subtracting the total weight (A) of the porous polytetrafluoroethylene film and the string measured in advance from the weight of this sample. The adhesive sample wrapped in the porous polytetrafluoroethylene film was immersed in approximately 50 mL of ethyl acetate at 23°C for 7 days, and the sol component of the adhesive was eluted outside the porous polytetrafluoroethylene film. After immersion, the adhesive wrapped in the porous polytetrafluoroethylene film was taken out, dried at 130°C for 2 hours, and allowed to cool for approximately 20 minutes, and then the dry weight (C) was measured. The gel fraction of the adhesive was calculated by the following formula. Gel fraction (%) = 100 × (CA) / B
[0123] For adhesive sheets A to C, the cumulative light intensity on the adhesive sheet is approximately 3000 mJ / cm2 The gel fraction was also measured for the adhesive photocured by irradiating it with ultraviolet light.
[0124] <Nanoindentation measurement of the edge surface of the adhesive layer> The laminates of the examples and comparative examples were cut at a position 3 mm from the end face to prepare a measurement sample. The sample was fixed on the stage of a nanoindentation system (Hysitron's "TI950 TriboIndenter") so that the end face of the laminate was the measurement surface. In an environment of 25°C and 50% relative humidity, a conical-spherical indenter (tip curvature radius: 10 μm) was used to indent to a depth of 3000 nm at a loading speed of 1000 nN / s and to pull up at an unloading speed of 1000 nN / s to perform the test. From the obtained load-displacement curve, the minimum load in the loading curve, the indentation elastic modulus, and the displacement of the unloading curve were obtained. The indentation elastic modulus E was calculated from the slope of the unloading curve, the projected contact area A of the indenter, and the circular constant π according to the following formula. E = (S√π) / (2√A)
[0125] <Tackiness of the edge> A 50 μm thick PET film that had not been subjected to surface treatment was cut into a size of 5 mm × 10 mm and placed on a horizontal table. The end face (cut face) of the optical laminate was pressed against the surface of the PET film, and then the end face was pulled up to evaluate the tackiness of the end face based on the adhesion state between the end face of the optical laminate and the PET film according to the following criteria. Good: The end face of the optical laminate and the PET film were not adhered to each other, and the optical laminate could be pulled up without resistance. △: When the optical laminate was pulled up, the PET film was not lifted, but peel resistance was felt between the end face of the optical laminate and the PET film. ×: The edge of the laminate and the PET film remained in an adhesive state, and the PET film was lifted up.
[0126] <Pickup test> Ten optical laminates were stacked with the polyimide film side facing downward. A suction cup was pressed against the upper side (the side facing the release film) of the stacked adhesive sheets to adsorb the laminates, and the topmost stacked laminate was lifted up with the suction cup to pick it up. It was confirmed whether or not only one optical laminate could be picked up, and the pick-up ability was evaluated according to the following criteria. 〇: Only one laminate was picked up △: The laminate just below the picked up laminate rose up, but then separated and only one sheet could be picked up. ×: Two or more laminates were lifted together and could not be picked up one by one.
[0127] Table 1 shows the gel fraction of the adhesive of each of the optical laminates obtained above (before and after photocuring), the cutting method into chips, and the evaluation results.
[0128] [Table 1]
[0129] When the chips of laminates A and B were cut by punching, the cut surface had tackiness, resulting in poor pick-up, but when the chips were cut by ultraviolet laser processing, there was no tackiness on the end surface, and they showed good pick-up properties. In laminates A and B, the end surface processed by laser had a higher elastic modulus, and the absolute value of the minimum load on the load curve and the displacement of the unload curve were smaller than those processed by punching. From these results, it is believed that the end surface of the chips of laminates A and B was hardened by laser processing, which reduced the stickiness of the end surface of the adhesive layer.
[0130] In laminate C, which used an adhesive with a small gel fraction before photocuring, the cut surface had tackiness and pickup problems occurred both when the chips were cut out by punching and when they were cut out by laser processing. In addition, laminate D, which used an adhesive that did not have photocuring properties, also had problems with pickup properties.
[0131] In laminate C, even though the adhesive has photocuring properties, the edge did not harden even when cut with an ultraviolet laser, and instead, cutting with a laser showed a decrease in elastic modulus and an increase in the displacement of the unloading curve (stringiness), indicating plasticization. In laminate C, the gel fraction of the adhesive is small, so the effect of molecular cutting by laser irradiation (generation of low molecular weight components) became dominant, which is thought to be the cause of the softening of the adhesive.
[0132] In laminate D, the adhesive was not photocurable, but the displacement of the unloading curve was smaller when the chips were cut by laser processing than when the chips were cut by punching. A comparison of laminates C and D shows that in order to obtain a laminate by laser processing that does not have sticky edges of the adhesive layer, it is important that not only the adhesive be photocurable, but also that the gel fraction of the adhesive be large. [Explanation of symbols]
[0133] 10 Optical film (polarizing plate) 11 Polarizer 13,15 Transparent film 21, 22 Adhesive layer 41, 42, 43 Release film 70 Image display cell (organic EL cell) 71 Substrate (polyimide film) 80 Cover Window 101,102,103,104,105 Optical laminate
Claims
1. preparing a mother substrate of an optical laminate including a first pressure-sensitive adhesive layer having a first main surface and a second main surface, a first adherend bonded to the first main surface of the first pressure-sensitive adhesive layer, and a second adherend bonded to the second main surface of the first pressure-sensitive adhesive layer; A method for producing an optical laminate, comprising cutting the mother substrate into chips having a size smaller than that of the mother substrate, The adhesive constituting the first adhesive layer contains a base polymer and further contains a monomer or oligomer having a photocurable functional group, or a compound having a photocurable functional group is bonded to the base polymer, so that the adhesive has photocurability; When cutting the mother substrate, an ultraviolet laser is irradiated onto the mother substrate to cut the optical laminate and photo-cure the first pressure-sensitive adhesive layer on the cut surface. In the optical laminate after cutting, the cut surface of the first pressure-sensitive adhesive layer has a minimum load of −0.2 μN or more in a load curve measured by nanoindentation, and a displacement of an unloading curve of 8 μm or less; A method for producing an optical laminate, wherein the displacement of an unloading curve of a cut surface of the first adhesive layer measured by nanoindentation is 0.5 times or less the displacement of an unloading curve of a central portion of the surface.
2. A method for manufacturing an optical laminate as described in claim 1, wherein in the optical laminate after cutting processing, the first adhesive layer has a gel fraction of the adhesive in the central part of the surface of 25% or more.
3. A method for manufacturing an optical laminate as described in claim 1 or 2, wherein in the optical laminate after cutting, the absolute value of the minimum load of the load curve on the cut surface measured by nanoindentation of the first adhesive layer is 0.3 times or less the absolute value of the minimum load of the load curve at the center of the surface.
4. The method for producing an optical laminate according to any one of claims 1 to 3, wherein the first pressure-sensitive adhesive layer contains an ultraviolet absorber.
5. The method for producing an optical laminate according to any one of claims 1 to 4, wherein the first pressure-sensitive adhesive layer has a thickness of 30 µm or more.
6. The method for producing an optical laminate according to any one of claims 1 to 5, wherein the second adherend has a polarizing plate in contact with the first pressure-sensitive adhesive layer.
7. The method for producing an optical laminate according to claim 6 , wherein the second adherend further includes an image display cell attached to the polarizing plate via a second pressure-sensitive adhesive layer.
8. The method for producing an optical laminate according to claim 7 , wherein the image display cell is an organic EL cell.
9. The method for producing an optical laminate according to claim 7 or 8, wherein the image display cell comprises a polyimide film.
10. The method for producing an optical laminate according to any one of claims 1 to 9, wherein the first adherend is a release film releasably attached to the first pressure-sensitive adhesive layer.
Citation Information
Patent Citations
Adhesive composition for optical member, adhesive layer, optical member having adhesive layer, image display with optical member, and method of manufacturing image display device
JP2011241377A
Long rolled polarizing plate, method for manufacturing liquid crystal display device, and liquid crystal display device
JP2012058433A
Manufacturing method for optical laminate with adhesive layer
JP2012063775A
Pressure-sensitive adhesive composition, and optical member using the same
JP2012140587A
Pressure-sensitive adhesive, pressure-sensitive adhesive sheet and optical film with pressure-sensitive adhesive
JP2012153901A